Effect of a single, oral administration of selenitetriglycerides, at two dose rates, on blood selenium status and haematological and biochemical parameters in Holstein-Friesian calves - Żarczyńska, Katarzyna; Sobiech, Przemysław; Tobolski, Dawid; Mee, John F; Illek, Josef (Irish veterinary journal, 2021)
BACKGROUND: Selenitetriglycerides are biologically active, organic forms of selenium formed as a result of the modification of selenic acid and sunflower oil. Studies in rats have shown that they are well absorbed and of low toxicity. There are no published studies on selenitetriglycerides supplementation in calves. RESULTS: In this study, selenitetriglycerides were administered once orally on the 2nd day of life at a dose of 0.5 or 1 mg Se/kg body weight to each of six Holstein-Friesian calves while six control calves were not supplemented. Blood for determination of selenium concentration, glutathione peroxidase activity, haematological parameters, aspartate aminotransferase, creatine kinase, and lactate dehydrogenase activities and glucose, total protein, albumin, triglycerides, cholesterol, urea, and creatinine concentration was collected before supplementation (day 0) and 1, 2, 5, 10 and 14 days after supplementation. Selenitetriglycerides administration increased (P < 0.01) serum selenium concentration in supplemented calves as early as day1, from a mean of 63.4 to 184.22 µg/l in calves receiving selenium at a dose of 0.5 mg/kg BW, and from 63.17 to 200.33 µg/l in calves receiving 1 mg/kg. Serum selenium concentrations remained significantly higher compared to the control group throughout the experiment. Glutathione peroxidase activity was higher in supplemented than control calves, significantly so in animals receiving the 1 mg/kg dose of Se on the 10th and 14th days (P < 0.05). There were no significant differences in the haematological and biochemical parameters between the groups. CONCLUSIONS: This experiment showed that supplementation with selenitetriglycerides could significantly improve blood selenium status in calves without adverse effects on haematological or biochemical parameters. These findings are essential prerequisites for future studies on selenitetriglycerides supplementation to manage clinical selenium deficiency in calves.
Keywords: Calves; Selenitetriglycerides; Biochemical parameters; Glutathione peroxidase; Selenium; Haematology